2014
DOI: 10.1007/s11595-014-1040-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and arc erosion resistance of Cf/Cu composite by vacuum melting infiltration

Abstract: C f /Cu composite was prepared by vacuum melting infi ltration. Ti and Cr were doped to the Cu alloy to improve the wettability between Cu and carbon. The microstructure was investigated by XRD, SEM and EDS. The arc erosion rate of C f /Cu composite was investigated in vacuum. The results showed that the Ti and Cr could improve the wettability between Cu and C/C preform and the infi ltration ability of Cu into C/ C preform greatly. A TiC interface formed between the fi bers and matrix. The good bonding between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In order to increase the wettability between the interfaces, the most preferred method is to alloy the copper. According to the literature, titanium is the most prominent as an alloying carbide forming element [34][35][36][37][38][39][40]. Apart from this, it has been observed that Cr and Si elements are also used [32,41,42].…”
Section: Addition Of Elements Into Coppermentioning
confidence: 99%
See 3 more Smart Citations
“…In order to increase the wettability between the interfaces, the most preferred method is to alloy the copper. According to the literature, titanium is the most prominent as an alloying carbide forming element [34][35][36][37][38][39][40]. Apart from this, it has been observed that Cr and Si elements are also used [32,41,42].…”
Section: Addition Of Elements Into Coppermentioning
confidence: 99%
“…Zhang Huayu and Yiwen Liu [35] worked with the same materials and process to produce Cu-C composites. They examined the arc erosion resistance of these composites.…”
Section: Addition Of Elements Into Coppermentioning
confidence: 99%
See 2 more Smart Citations